Interlinkages between Energy, Environmental Changes and Livelihoods in Laotian Households : Findings from 14 Focus Group Discussions - Khanthapath, Bouasavanh; Lakkala, Hanna; Luukkanen, Jyrki (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This publication presents and discusses the findings of 14 focus group discussions (FGD) conducted in different parts of Laos in early 2011 as a part of the project “Interlinkages Between Energy and Livelihoods – Data, Training and Scenarios for Sustainable Energy Planning in Laos (INES)”, which is a project funded by the Finnish Ministry for Foreign Affairs and Nordic Development Fund in the framework of Energy and Environment Partnership (EEP) Mekong in South East Asia. The INES project was implemented by Finland Futures Research Centre (FFRC) in cooperation with the Ministry of Energy and Mines of Laos. The overall objective of the project is to improve the capacity of decision makers in Laos to promote sustainable long-term energy planning. In addition, the aim has been to provide qualitative and quantitative data on rural and urban resources and livelihood strategies and increase the knowledge of energy resources and use, and sustainable use of natural resources in Laos.